The Effectiveness of the Group Investigation Learning Model with Mind Mapping to Improve Students' Motivation and Learning Outcomes on Animalia Materials in SMA - Anggun Novita Ciptasari; Retno Sri Iswari (Journal of Biology Education, 2023)
Student learning outcomes on the material Kingdom Animalia are low. Students who are able to achieve the minimum completeness criteria are only 0,69% of the total population. It turns out that many students find it difficult to understand the concept of 41,67%. This means that the teacher must be able to attract students' interest and curiosity about the material. The Group Investigation (GI) Learning Model with Mind Mapping is able to generate low student motivation. The purpose of this research is to analyze the effectiveness of the Group Investigation (GI) learning model with Mind Mapping on increasing students' motivation and learning outcomes in the Animalia class X material at SMA Negeri 1 Blora in the 2021/2022 academic year compared to the conventional model. The research carried out is experimental research. The research experimental design used is a quasi-experimental design using a nonequivalent groups pretest-posttest control design design groups. The population of class X students in the even semester of SMA N 1 Blora was taken two classes as samples with the technique of simple random sampling. Class X Mipa 1 was selected as the experimental class and class X Mipa 2 was selected as the control class. Research data in the form of student motivation, student learning outcomes, and student responses to the learning process. Existing data were analyzed by t-test. The results showed that after treatment, students' learning motivation in the experimental class (3,21 or 80,28%) was better than the control class (3,00 or 74,97%). The results of the t-test calculation obtained indicate that there is a significant difference between increased motivation in the experimental class and the control class. The average N-Gain value for the experimental class is 0,56 or 56,02%, while in the control class the average N-Gain value is 0,33 or 32,96%. The results of the t-test analysis showed that the experimental class learning outcomes were significantly higher than the control class. The results of classical completeness in the experimental class were 83,33%, while the control class obtained 41,67% results. Students gave a good response to the implementation of learning using the Group Investigation (GI) learning model with Mind Mapping. The conclusion of this research is that the application of the Group Investigation (GI) learning model with Mind Mapping is effective in increasing students' motivation and learning outcomes in Animalia material compared to conventional models.